Metabolic and molecular signatures of improved growth in Atlantic salmon (Salmo salar) fed surplus levels of methionine, folic acid, vitamin B6 and B12 throughout smoltification. Issue 9 (14th May 2022) - Adam, Anne-Catrin; Saito, Takaya; Espe, Marit; Whatmore, Paul; Fernandes, Jorge Manuel De Oliveira; Vikeså, Vibeke; Skjærven, Kaja H.
Abstract : Abstract: A moderate surplus of the one carbon (1C) nutrients methionine, folic acid, vitamin B6 and B12 above dietary recommendations for Atlantic salmon has shown to improve growth and reduce hepatosomatic index in the on-growing saltwater period when fed throughout smoltification. Metabolic properties and molecular mechanisms determining the improved growth are unexplored. Here, we investigate metabolic and transcriptional signatures in skeletal muscle taken before and after smoltification to acquire deeper insight into pathways and possible nutrient–gene interactions. A control feed (Ctrl) or 1C nutrient surplus feed (1C+) were fed to Atlantic salmon 6 weeks prior to smoltification until 3 months after saltwater transfer. Both metabolic and gene expression signatures revealed significant 1C nutrient-dependent changes already at pre-smolt, but differences intensified when analysing post-smolt muscle. Transcriptional differences revealed lower expression of genes related to translation, growth and amino acid metabolisation in post-smolt muscle when fed additional 1C nutrients. The 1C+ group showed less free amino acid and putrescine levels, and higher methionine and glutathione amounts in muscle. For Ctrl muscle, the overall metabolic profile suggests a lower amino acid utilisation for protein synthesis, and increased methionine metabolisation in polyamine and redox homoeostasis, whereas transcription changes are indicative of compensatory growth regulation at local tissue level. These findings point to fine-tuned nutrient–gene interactions fundamental for improved growth capacity through better amino acid utilisation for protein accretion when salmon was fed additional 1C nutrients throughout smoltification. It also highlights potential nutritional programming strategies on improved post-smolt growth through 1C+ supplementation before and throughout smoltification.